2018
DOI: 10.1007/s00415-018-8871-2
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab as rescue therapy in a cohort of 50 relapsing–remitting MS patients with breakthrough disease on fingolimod: a multi-center observational study

Abstract: Therapy switch was highly effective in reducing clinical and MRI surrogates of disease activity and was mainly well tolerated within one year of follow-up. Hence, alemtuzumab constitutes a promising therapy in RRMS with refractory disease activity despite fingolimod treatment. Further studies are warranted to confirm these beneficial findings and to reveal safety concerns in the longer-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
5
22
1
2
Order By: Relevance
“…A case of severe disease reactivation 19 days after infusion of rituximab 1 g after a 6-week fingolimod washout has been reported, suggesting that a 6-week washout period may be too long in some patients [53]. In one cohort, 9/36 patients with highly active MS who switched from fingolimod to alemtuzumab had significant disease activity during the first year of alemtuzumab treatment [54], but larger cohorts have found alemtuzumab to be an effective option after fingolimod [55,56].…”
Section: Choice Of Next Therapymentioning
confidence: 99%
“…A case of severe disease reactivation 19 days after infusion of rituximab 1 g after a 6-week fingolimod washout has been reported, suggesting that a 6-week washout period may be too long in some patients [53]. In one cohort, 9/36 patients with highly active MS who switched from fingolimod to alemtuzumab had significant disease activity during the first year of alemtuzumab treatment [54], but larger cohorts have found alemtuzumab to be an effective option after fingolimod [55,56].…”
Section: Choice Of Next Therapymentioning
confidence: 99%
“…A retrospective analysis of 50 patients transitioning from fingolimod to alemtuzumab showed a strong reduction in disease activity within 12 months after the switch. 26 However, in another series of patients treated sequentially with fingolimod and then alemtuzumab, nine were identified as experiencing disease activity within 12 months after alemtuzumab Course 1. 27 Even though animal studies showed some degree of lymphocyte depletion in lymph nodes after alemtuzumab administration, 8 the authors speculated that residual sequestration in lymph nodes after cessation of fingolimod treatment could protect lymphocytes from alemtuzumab-mediated depletion and contribute to persistence of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been case reports of clinical worsening after switching from fingolimod to ocrelizumab, rituximab, or alemtuzumab. [150][151][152] Conversely, there are reports that rituximab and alemtuzumab are effective in patients with an inadequate response to fingolimod, 153,154 although persistent T cell depletion may occur after a fingolimod-alemtuzumab switch. 155 A washout period has traditionally been recommended when switching among second-line agents to allow lymphocyte counts and other indices (e.g., liver enzymes) to return to normal.…”
Section: Treatment Sequencingmentioning
confidence: 99%